Buddhist Methods for Promoting Public Participation in the Zero Waste Project Implementation in Muang Sam Sip Subdistrict Municipality, Muang Sam Sip District, Ubon Ratchathani Province - Sirivaḍḍhano (Karanan), Phra Siriwat; Promgun, Suraphon; Sawatta, Sutipong (Journal of Buddhist Education and Research (JBER), 2025)
This thesis aimed to: 1) study the level of Buddhist methods for promoting public participation in the Zero Waste Project implementation in Muang Sam Sip Subdistrict Municipality, Muang Sam Sip District, Ubon Ratchathani Province; compare Buddhist methods for promoting public participation in the Zero Waste Project implementation based on personal factors; 3) present Buddhist methods for promoting public participation in the Zero Waste Project implementation in Muang Sam Sip Subdistrict Municipality, Muang Sam Sip District, Ubon Ratchathani Province. This research employed a mixed-method approach, integrating both quantitative and qualitative methods. The quantitative study involved a survey of 347 respondents using a questionnaire. Data analysis utilized frequency, percentage, mean, and standard deviation, with hypothesis testing conducted through t-test and F-test. The qualitative component included in-depth interviews with 12 key informants, with data analyzed using descriptive content analysis. The research results were as follows: 1. The level of public participation in the Zero-Waste project implementation: Overall, public participation in the Zero Waste Project implementation was high, with a mean score of 4.10. Analyzing different aspects, all were rated at a high level. The highest mean score was for benefit-sharing participation (4.12), followed by community participation (4.10), operational participation (4.10), evaluation participation (4.10), and planning participation (4.08), respectively. 2. Comparison of Buddhist methods for promoting public participation in the Zero-Waste project: The study found that citizens with differences in gender, age, education level, occupation, average monthly income, and adherence to the Four Bases of Success (Iddhipāda 4) showed statistically significant differences (p < 0.01) in their level of participation in the Zero Waste Project, confirming the research hypothesis. 3. Buddhist methods for promoting public participation in the Zero Waste Project Implementation: (1) Raising awareness of waste management, recognizing the importance of waste and pollution issues, and appreciating various operational mechanisms, including policies, project implementation, and effectiveness evaluation. (2) Ensuring continuous implementation under beneficial policies, which leads to efficient waste management. A systematic and sustained approach is crucial for maximizing waste management effectiveness. (3) Fostering commitment and dedication to waste management work, encouraging a systematic approach to waste administration. (4) Understanding waste management challenges and applying a compassionate and reasoned approach in operations, critically evaluating issues, identifying shortcomings, and making necessary improvements for future development.